Dignity - R. Graham (South African Family Practice)
It is important to consider, albeit occasionally, issues, words or concepts commonly utilised in medicine. Dignity, is a word or, probably more correctly a concept that one now only occasionally encounters. Death with dignity is used in justification of euthanasia, while some arguments may claim that cloning is an affront to human dignity. Dignity is also regularly referred to in aspirational, philosophical or legal texts.